2014
DOI: 10.1111/bjh.12763
|View full text |Cite
|
Sign up to set email alerts
|

MYC and BCL2 protein expression predicts survival in patients with diffuse large B‐cell lymphoma treated with rituximab

Abstract: SummaryDiffuse large B-cell lymphoma (DLBCL) is a heterogeneous disease and "double-hit" DLBCL, with both MYC and BCL2 translocations has a poor prognosis. In this study, we investigated whether MYC and BCL2 protein expression in tissue would predict survival in DLBCL. The study included 106 cases of de novo DLBCL treated with rituximab and cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) or CHOP-like regimens. The results were validated on an independent cohort of 205 DLBCL patients. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
140
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 37 publications
13
140
3
3
Order By: Relevance
“…Prior studies indicated that discrepant cases were resolved through group review at multi-headed microscope but did not provide any further details. 9,10,13 As staining heterogeneity is the most significant factor causing discrepancy, specific instructions on how to address this problem are needed to improve concordance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies indicated that discrepant cases were resolved through group review at multi-headed microscope but did not provide any further details. 9,10,13 As staining heterogeneity is the most significant factor causing discrepancy, specific instructions on how to address this problem are needed to improve concordance.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] These studies have shown that cases of diffuse large B-cell lymphoma with concurrent overexpression of MYC and BCL2 proteins have a dismal prognosis similar to those with double-hit lymphomas. The rate of so-called double-hit lymphoma-like cases as determined by immunohistochemistry is larger than the one detected by FISH.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,13,[22][23][24] Furthermore, the poor prognosis associated with Myc overexpression was contributed by cases with Myc/Bcl-2 coexpression-'doublepositive lymphoma' (DPL)-which account for 18-44% of DLBCLs. 13,20,[23][24][25][26] However, one study showed that the prognostic value of double-positive lymphoma was lost in younger DLBCL patients with poor prognosis. 27 Inconsistent results have been reported regarding whether the prognostic significance of Myc or Myc/Bcl2 protein expression depends on MYC or MYC/BCL2 gene rearrangement status or not.…”
mentioning
confidence: 99%